Optimisation of rice bran hydolysation using xylanase for xylooligosacchride production - Phuong, Nguyen Thi Mai; Anh, Nguyen Hoa; Ngoc, Pham Thi; Lien, Quach Thi; Bich, Nguyen Thi (Academia Journal of Biology, 2018)
Rice bran is a subsidised product of rice processing. It is rich in carbohydrate, especially xylan therefore, has being used for production of soluble fiber oligosaccharide including xylooligosaccharides (XOS). XOS is an oligomer of 2-7 xylose residues and has been proven to be fermented by beneficial bacteria Bifidobacterium and Lactobacillus in colon. The market for XOS is increasing rapidly due to its advantages in biological and technological properties, compared to other common oligosaccharides, such as fructooligosaccharide or galactooligosaccharide. XOS can be produced from rice bran using either chemical or enzymatic hydrolysation technologies. The hydrolyzation using β-1,4-xylanase is commonly used to produce XOS from rice bran. However, an appropriate technology for XOS production from rice bran with high purity and food safety in Vietnam is not available yet. This paper presents new data on optimisation of rice bran hydrolyzation by xylanase to produce XOS using the quadratic model of Box-Behnken. The theoretically optimized conditions for the hydrolyzation are 0.25% enzyme at pH 5.5, temperature of 50°C for 18 hours. Experimental data confirmed the selected condition. The XOS product contains mainly xylobiose, xylotriose and xylotetraose.